A review of platelet-rich plasma for enteric fistula management - Liang, Shuang; Zheng, Zhiqiang; Li, Yaxin; Yang, Yuanming; Qin, Lifeng; Zhao, Zhen; Wang, Licun; Wang, Haiyan (Frontiers in Bioengineering and Biotechnology, 2023)
Enteric fistula (EF), a serious complication after abdominal surgery, refers to unnatural communication between the gastrointestinal tract and the skin or other hollow organs. It is associated with infection, massive fluid/electrolyte loss, and malnutrition, resulting in an unhealed course. Despite advances in surgical techniques, wound care, infection control, and nutritional support, EF remains associated with considerable morbidity and mortality. Autologous platelet-rich plasma (PRP) containing elevated platelet concentrations has been proposed to promote healing in many tissues. However, the mechanism of action of PRP in EF treatment remains unclear owing to its complicated clinical manifestations. In this review, we summarized the clinical approaches, outlined the principal cytokines involved in the healing effects, and discussed the advantages of PRP for EF therapy. In addition, we defined the mechanism of autologous PRP in EF management, which is essential for further developing EF therapies.